Development of Interactive PPT Media Based on Audio Visual Using the Problem Based Learning Model to Improve Learning Outcomes of the Forces Around Us Material in Grade IV - Yunisa Ifvaranindra; Isa Ansori (Jurnal Penelitian Pendidikan IPA, 2024)
The problem in SD Negeri 02 Sidorejo, Pemalang Regency, is that teachers still use learning media that do not utilize technology that affects student learning outcomes. The purpose of this study is to develop interactive PPT media based on audiovisual using the PBL model, to determine its feasibility and effectiveness. Using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were students and teachers of grade IV of SD Negeri 02 Sidorejo. Data collection was carried out through test and non-test techniques with data analysis in the form of product analysis. The results of the expert validator's assessment were very feasible to obtain a percentage of 87%, while the media expert gave a percentage of 93%. The data is normally distributed with values The data is normally distributed, with values of 0.54 and 0.98 significance on the small-scale pretest and posttest and for a large scale of 0.31 and 0.10. The results of the t-test with significance (α) below 0.05 are 0.008 and 0.000. In the average increase test, the N-gain value was obtained at 0.67 on a large scale so that the effectiveness value was in the medium category. On a small scale, the mean value was 0.65, which was in the medium category. The conclusion of this study is that it is very feasible and improves learning outcomes. It is recommended that interactive PPT media based on audiovisual with the PBL model can be used by teachers as a learning medium so that learning objectives are achieved.